Reading Duncan reading : Robert Duncan and the poetics of derivation - Collis, Stephen, 1965-; Lyons, Graham (Contemporary North American poetry series, 2012)
In this book, thirteen scholars and poets examine, first, what and how the American poet Robert Duncan read and, perforce, what and how he wrote. Harold Bloom wrote of the searing anxiety of influence writers experience as they grapple with the burden of being original, but for Duncan this was another matter altogether. Indeed, according to Stephen Collis, "No other poet has so openly expressed his admiration for and gratitude toward his predecessors." The essays collected here trace paths of poetic affiliation and affinity and hold them up as provocative possibilities in Duncan's own inexhaustible work.